2015
DOI: 10.1097/cji.0000000000000097
|View full text |Cite
|
Sign up to set email alerts
|

Lenalidomide Synergistically Enhances the Effect of Dendritic Cell Vaccination in a Model of Murine Multiple Myeloma

Abstract: We investigated the efficacy of lenalidomide (LEN) in combination with dendritic cell (DC) vaccination in the MOPC-315 murine myeloma model. After tumor growth, LEN was injected intraperitoneally for 4 consecutive days in combination with DC vaccination. The combination of LEN and vaccination efficiently inhibited tumor growth compared with the single agents alone. A cytotoxic assay revealed that the anticancer effects of DC vaccination plus LEN involved not only generation of antigen-specific cytotoxic T lymp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 4 publications
2
40
1
Order By: Relevance
“…These critical immune suppressive checkpoint molecules are significantly elevated in patient MM cells vs normal PCs and further support MM cell growth and survival, as well as inhibit various effector cellmediated anti-MM immune responses. [63][64][65][66][67][68][69][70][71][72] For example, PD-L1 is induced in MM cells by interferon g, IL-6, and stromal cells. [64][65][66]73 It increases tumor growth and mediates tumor-induced immune inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…These critical immune suppressive checkpoint molecules are significantly elevated in patient MM cells vs normal PCs and further support MM cell growth and survival, as well as inhibit various effector cellmediated anti-MM immune responses. [63][64][65][66][67][68][69][70][71][72] For example, PD-L1 is induced in MM cells by interferon g, IL-6, and stromal cells. [64][65][66]73 It increases tumor growth and mediates tumor-induced immune inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the down-regulation of B cell counts by lenalidomide may be linked to its activity in B cell malignancies. In our previous study, lenalidomide synergistically enhanced the anticancer immunity of DC vaccination in a murine multiple myeloma (MM) model by inhibiting immunosuppressor cells, stimulating effector T and NK cells and inducing strong Th1-type immunity [29]. …”
Section: Discussionmentioning
confidence: 99%
“…Thus, we considered that the use of lenalidomide may enhance the tumor microenvironment and danger signals for generating potent Th1-type immune responses and antitumor immunity. Recently, several DC-based vaccines using known tumor antigens in mouse colon cancer models have been documented [16, 17, 2932]. In our study, dying tumor cells were used to load DCs to generate tumor-specific CTLs in tumor-bearing mice.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, it has been reported that DC play a dual opposite role as promoter of CD8+ T cells-mediated MM cell killing and as facilitator of MM cell resistance to CD8(+) T-cell killing [36]. Additionally, a positive effect in DC activation mediated by Lenalidomide treatment has been observed in both MM patients [37] and murine MM model [38]. Macrophages represent an important population in the MM microenvironment [39].…”
Section: Mechanisms Used By MM Cells To Suppress Nk Cell Functionsmentioning
confidence: 99%